Influence of hamstring extensibility on sagittal spinal curvatures and pelvic tilt in highly trained young kayakers - Lopez-Minarro, P. A.; Muyor, J. M.; Alacid, F. (European Journal of Sport Science, 2012)
Objective: To evaluate the influence of hamstring extensibility on spinal and pelvic postures adopted by young paddlers in their kayaks.